Floating city : a Nicholas Linnear novel - Lustbader, Eric 1946- (Nicholas Linnear, 1994)
In this sequel to The Kaisho & The Ninja, Nicholas Linnear returns to Vietnam where he confronts his most formidable challenge:a secret empire deep within the jungle, headed by an American killing machine named Rock who is bent on destroying the world.